Risk factors for puerperal sepsis among postpartum women attending public hospitals in the Dawro Zone, Southwest Ethiopia: Unmatched case‒control study - Temesgen Sebro Balilo; Tsegaye Alemu; Tamirat Gezahegn Guyo; Tarekegn Solomon (Women's Health)
Background: Puerperal sepsis is a severe bacterial infection that occurs in women between the beginning of labor or rupture of the membrane and the 42 nd day following birth. In Ethiopia, it is the fourth leading cause of maternal death, accounting for 14.7% of pregnancy-related deaths. The risk factors for puerperal sepsis are not well understood in Ethiopia, particularly in southwestern Ethiopia. Objectives: This study aimed to identify risk factors for puerperal sepsis among postpartum women at public hospitals in the Dawro Zone, Southwest Ethiopia. Design: A facility-based unmatched case–control study. Methods: From February 1 to April 30, 2023, 260 participants (65 cases and 195 controls) were included in the study. The cases were postpartum women who were diagnosed with puerperal sepsis, whereas the controls were postpartum women confirmed to be free from puerperal sepsis. Cases selected consecutively, and controls enrolled via systematic random sampling. Data were collected via an interviewer-administered questionnaire and medical records review. STATA version 17 was used for analysis. The associations between variables were analyzed via a binary logistic regression model. A p value <0.05 was considered statistically significant. Results: Rural residence (adjusted odds ratio (AOR): 3.62; 95% confidence interval (CI): 1.40, 9.33), no formal education (AOR: 4.40; 95% CI: 1.25, 15.49) compared with college or above, no antenatal care (ANC; AOR: 14.04; 95% CI: 4.56, 43.20) compared with three or more ANC visits, prolonged rupture of the membrane above 24 h (AOR: 9.51; 95% CI: 2.49, 36.35), home delivery (AOR: 3.06; 95% CI: 1.26, 7.49), ⩾5 vaginal examinations (AOR: 7.44; 95% CI: 2.77, 19.94), and cesarean section (AOR: 2.89; 95% CI: 1.13, 7.42) were significantly associated with the puerperal sepsis. Conclusions: Rural residence, lack of formal education, lack of ANC follow-up, prolonged rupture of membrane, home deliveries, frequent vaginal examinations, and cesarean section deliveries increase puerperal sepsis. Targeted intervention requires on modifiable risk factors such as ensuring at least on ANC, promoting institutional delivery, ensuring timely administration of appropriate antibiotics for prolonged rupture of membrane, avoiding unnecessary vaginal examinations and cesarean section.